Decomplexation Performance of Cu–EDTA and Parameter Optimization by Three-Dimensional Electro-Fenton - Ma, Yameng; Huang, Xiao; Han, Qi; Yu, Jianghua; Yu, Fengjiao; Zhu, Jia (Frontiers in Environmental Science, 2022)
The strong stability of Cu–ethylenediaminetetraacetic acid (Cu–EDTA) results in the low decomplexation efficiency by the traditional Fenton process. For breaking this limitation, a three-dimensional electro-Fenton (3D-EF) system was constructed to study the decomplexation of Cu–EDTA at different pH, and the effects of Fe2+ concentration, particle electrode dosage, current density, and coexisting ions on decomplexation performance were investigated. The results showed that 3D-EF exhibited high pollutant removal efficiency in a wide pH range compared with the traditional electro-Fenton process. The optimal conditions for the removal of Cu–EDTA were as follows: the pH was 7, Fe2+ was 1 mmol L−1, granular activated carbon was 2 g L−1, and current density was 10 mA cm−2, and the optimum Cu–EDTA removal efficiency reached 90.95%. In addition, the presence of Cl− slightly improved the decomplexation efficiency, whereas NO3− and HPO42− inhibited the removal of Cu–EDTA. The kinetics of Cu–EDTA decomplexation in all experimental groups followed the first-order kinetic equation.